2017
DOI: 10.1155/2017/5259849
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Wharton’s Jelly-Derived Mesenchymal Stem Cell’s Survival, Migration, and Expression of Wound Repair Markers under Conditions of Ischemia-Like Stress

Abstract: The efficacy of mesenchymal stem cell (MSC) therapy is currently limited by low retention and poor survival of transplanted cells as demonstrated by clinical studies. This is mainly due to the harsh microenvironment created by oxygen and nutrient deprivation and inflammation at the injured sites. The choice of MSC source could be critical in determining fate and cellular function of MSCs under stress. Our objective here was to investigate the influence of ischemia-like stress on Wharton's jelly MSCs (WJ-MSCs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The ability of cells to response to hypoxia is another important point to evaluate. WJ-MSCs have been previously proved to don't be affected by ischemia and they thus be considered as a promising source for clinical applications (Himal et al 2017). In this work, we observed an increased expression of HIF1a, HIF2a and GLUT1 in ALDH ?…”
Section: Discussionsupporting
confidence: 56%
“…The ability of cells to response to hypoxia is another important point to evaluate. WJ-MSCs have been previously proved to don't be affected by ischemia and they thus be considered as a promising source for clinical applications (Himal et al 2017). In this work, we observed an increased expression of HIF1a, HIF2a and GLUT1 in ALDH ?…”
Section: Discussionsupporting
confidence: 56%
“…Umbilical cord mesenchymal stromal/stem cells (UC-MSCs) [19] were used based on the long history using perinatal tissue in (burn) wound care, its impressive healing capabilities [1,[20][21][22], and its easy accessibility. In addition, trials [22,23] have shown their safety [22][23][24], their superior multipotent potential compared to other MSC sources [25], their excellent immunosuppressive properties with a low risk of graft-versus-host disease [26], and their potency under ischemic-like stress conditions [27].…”
Section: Msc Preparationmentioning
confidence: 99%
“…Later, another study proposed that ulinastatin was able to promote survival of MSCs under serum deprivation state [27], and similarly, BMP signaling pathway was indicated to be involved in survival of human MSCs in serum-free medium [28]. We also recently showed that WJ-MSCs retained a significant level of viable cells under the harsh ischemia-like conditions in vitro, with a strong upregulation of VTN [7].…”
Section: Discussionmentioning
confidence: 88%
“…In a recent study of ours, we demonstrated that WJ-MSCs retained greater than 80% viable population under ischemia-like stress condition in vitro [7]. Survival of WJ-MSCs under this harsh, low-nutrient microenvironment was interesting, and hence, the underlying mechanism behind this survival strategy demanded further investigation.…”
Section: Introductionmentioning
confidence: 86%